Gentamicin-Loaded TiO2 Nanotubes as Improved Antimicrobial Surfaces for Orthopedic Implants - Draghi, Lorenza; Preda, Valeria; Moscatelli, Monica; Santin, Matteo; Chiesa, Roberto (Frontiers in Materials, 2020)
Titanium oxide nanotube arrays are extremely promising materials for localized drug delivery in orthopaedic implants because of their excellent properties and facile preparation. TiO2 nanotubes act as an effective drug reservoir for localized drug delivery and promote faster tissue regeneration, effective osseointegration while, at the same time, preventing bacterial adhesion and implant infection. Here, highly ordered TiO2 nanotubes (NTs) were synthesized by electrochemical anodization of Ti sheets and the process voltage was varied to obtain surfaces with different NTs diameters. The effect of NTs dimension on cell and bacterial adhesion and on gentamicin loading and release was assessed. Anodization was confirmed an easy and effective method to prepare highly ordered, open top nanotubes with predictable diameter as a function of imposed voltage. A lower number of bacteria Staphylococcus Aureus adhesion was found to be reduced on NTs surfaces and on smaller nanotubes in particular. When gentamicin was loaded, protracted release and antibacterial action was observed and bacteria were not observed, either in planktonic or adhered. Moreover, higher cell proliferation and a more favourable cell morphology were observed on smaller nanotubes, to further support the indication toward a reduction in NTs diameter for the preparation of effective implant surfaces.